PENERAPAN MODEL PROBLEM BASED LEARNING (PBL) BERBANTUAN MEDIA ALPHABET CARD DALAM PENINGKATAN KEMAMPUAN MEMBACA PERMULAAN SISWA KELAS I SD UNISMUH MAKASSAR - Mansyur, Muvida; Munir, Abdul; Agus, M (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This research was motivated by the low initial reading skills of first-grade students at Unismuh Elementary School in Makassar. Based on initial observations, it was found that students' reading abilities were still varied, with most students experiencing difficulties in initial reading, such as recognizing letters, reading syllables, and reading simple words. This study aims to improve students' early reading skills through the application of the Problem Based Learning (PBL) model assisted by Alphabet Card media. This study is a Classroom Action Research (CAR) conducted in two cycles, each consisting of planning, implementation, observation, and reflection stages. The subjects of the study were 21 first-grade students of Unismuh Makassar Elementary School. The results showed that the application of the PBL model assisted by Alphabet Card media can improve student activity and learning outcomes. Student activity showed a significant increase, marked by increased involvement, courage, and enthusiasm in learning. Students' early reading skills increased, where in the first cycle students' abilities were still varied, while in the second cycle most students had achieved learning mastery according to the Minimum Mastery Criteria (KKM) of 70. Thus, the application of the Problem Based Learning (PBL) model assisted by Alphabet Card media is effective in improving the first-grade students' early reading skills.